Late Life Depressive Symptoms and Cognitive Function among Older Mexican Adults: The Past and the Present - Saenz, Joseph L. (Aging Ment Health, 2018)
OBJECTIVE: To evaluate associations between depression and individual cognitive domains and how changes in depressive symptoms relate to cognition three years later in the context of Mexico, a developing country experiencing rapid aging. METHOD: Data comes from waves 3 (2012) and 4 (2015) of the Mexican Health and Aging Study (n=12,898, age 50+). Depression is ascertained using a modified Center for Epidemiologic Studies – Depression Scale. Cognition is assessed using verbal learning, verbal memory, visual scanning, verbal fluency, visuospatial ability, visual memory, and orientation tasks. Depressive symptoms and cognitive functioning were both measured in 2012 and 2015. Scores across cognitive domains are modeled using ordinary least squares regression, adjusting for demographic, health, and economic covariates. RESULTS: When depression and cognition were measured concurrently in 2015, depression exhibited associations with all cognitive domains. When considering a respondent’s history of depression, individuals who had elevated depressive symptoms in 2012 and recovered by 2015 continued to exhibit poorer cognitive function in 2015 in verbal learning, verbal memory, visual scanning, and verbal fluency tasks compared to individuals who were neither depressed in 2012 nor 2015. CONCLUSIONS: Depression was associated with cognition across cognitive domains among older Mexican adults. Despite improvements in depressive symptomatology, formerly depressed respondents continued to perform worse than their counterparts without a history of depression on several cognitive tasks. In addition to current mental health status, researchers should consider an individual’s history of depression when assessing the cognitive functioning of older adults.